Discernments literary essays, cultural critiques, and book reviews - Galan, Ralph Semino (Manila UST Publishing House, 2013)
Essays, critiques and book reviews.
Includes bibliographical index.
Keywords: Philippine literature (English) -- History and criticism; Philippine essays (English) -- History and criticism; Philippine poetry (English) -- History and criticism